Upper bounds of block ciphers resistance with randomized nodes change to linear and differential cryptanalysis methods - Кінзерявий, Василь Миколайович (Ukrainian Information Security Research Journal, 2013)
The theory analysis and basis of block ciphers resistance with fixed replacement nodes regard to the linear and differential cryptanalysis is quite developed.There are also block ciphers in which the nodes are defined by replacing the round key. It is clear that the using of randomized replacement nodes in ciphers makes difficult cryptanalysis for them, but it is difficult to assess quantitatively. Given this, the urgent task is to take the analytical expressions that allow to prove the practical resistance of block ciphers with randomized replacement nodes regard to the linear and differential cryptanalysis and will make a quantitative assessment of their effectiveness. In this paper obtain analytical upper bounds for the parameters characterizing the practical resistance of block ciphers with randomized replacement nodes regard to the linear and differential cryptanalysis. These estimates generalize previously known to block ciphers with randomized replacement nodes can explain increase resistance regard to these methods of cryptanalysis.